PREVALENCE of SALMONELLA SPP. ANTIBODIES TO TOXOPLASMA GONDII, and NEWCASTLE DISEASE VIRUS IN FERAL PIGEONS (COLUMBA LIVIA) IN THE CITY of JABOTICABAL, BRAZIL - de Sousa, Eliane [UNESP]; Berchieri, Angelo [UNESP]; Pinto, Aramis Augusto [UNESP]; Machado, Rosangela Zacarias [UNESP]; Torres Carrasco, Adriano de Oliveira; Marciano, Jose Antonio [UNESP]; Werther, Karin [UNESP] (Amer Assoc Zoo Veterinarians, 2010)
The rock pigeon (Columba livia) may serve as a reservoir for several pathogenic agents that can be transmitted to poultry, wildlife, domesticated pets, and/or humans via excreta, secretions, or dust from feathers. In addition, ingestion of infected pigeons by wild and domestic animals can also transmit these pathogenic agents. The health status of 126 free-living pigeons in an urban area was evaluated by microbiologic culture for Salmonella and serologic testing for the presence of antibodies for Toxoplasma gondii and for Newcastle disease virus (NDV) from 120 and 109 pigeons, respectively. After drawing blood, the birds were euthanized, and fragments of the liver, spleen, lungs, and gonads, and feces were cultured for Salmonella spp. Salmonella spp. was isolated from 10 birds (7.94%), of which 8 were Salmonella typhimurium, one was Salmonella enterica subsp. enterica serotype 4,12 and one was Salmonella enterica subsp. enterica serotype 4,12,i. Six of 109 pigeons (5.50%) were positive for NDV antibodies when using the hemagglutination inhibition test. Toxoplasma gondii antibodies were detected by immunofluorescence in one of 120 sera tested (0.83%). The results indicate that feral rock pigeons were exposed to NDV and T gondii, although the exposure was low. In addition, these birds had Salmonella spp. and could disseminate this pathogen in the environment.
Keywords: Columba livia; feral rock pigeon; Newcastle disease; Salmonella; Toxoplasma gondii